Elastomer spacers in fire conditions = Podkładki elastomerowe w warunkach pożarowych - Roszkowski, Paweł; Sędłak, Bartłomiej; Sulik, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper, fire resistance of linear joints seal made of elastomer spacers under standard fire conditions, and thermal degradation range of EPDM elastomeric spacers are investigated. The geometry of elastomer spacer joints is important not only for their load capacity under normal conditions - thickness, width, and cavity depth can also influence fire resistance performance.
Keywords: fire resistance; fire integrity; fire insulation; elastomer spacer; EPDM; thermal degradation; linear joint seal; odporność ogniowa; szczelność ogniowa; izolacyjność ogniowa; podkładka elastomerowa; degradacja termiczna; uszczelnienie złącza liniowego